2012
DOI: 10.1016/j.jallcom.2012.03.103
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes upon lithium insertion in Ni 0.5 TiOPO 4

Abstract: a b s t r a c tNickel titanium oxyphosphate Ni 0.5 TiOPO 4 (NTP), was prepared by co-precipitation route. Its structure was determined by single crystal X-ray diffraction. The compound crystallizes in the monoclinic system, S.G: P2 1 /c [a = 7.333(1)Å, b = 7.316(2)Å, c = 7.339(2)Å,ˇ= 119.62(3) • , Z = 4, R 1 = 0.0142, wR 2 = 0.0429]. The structure might be described as a {TiOPO 4 } framework made of corner-sharing [TiO 6 ] octahedra chains running parallel to [0 0 1] and cross linked by phosphate [PO 4 ] tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…On the other hand, the active materials after the 1st charge were changed into orthorhombic compound. The electrode surfaces after the 1st discharge were assigned to triclinic LiTiOPO 4 . The results were the same after the 10th charge and 10th discharge.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the active materials after the 1st charge were changed into orthorhombic compound. The electrode surfaces after the 1st discharge were assigned to triclinic LiTiOPO 4 . The results were the same after the 10th charge and 10th discharge.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…1 On the other hand, Ti-based MB 0.5 TiOPO 4 (MB = Fe, Co, Ni, or Cu) materials have been researched and developed as high-capacity anode materials for lithium secondary batteries. [2][3][4][5][6][7][8][9] Y. Kee and coworkers reported the synthesis of rhombohedral LiTi 2 (PO 4 ) 3 and orthorhombic Li 1.5 Ti 2 (PO 4 ) 3 via the sol-gel method and the investigation of their use as anode materials for rechargeable Liion batteries. 10 S. Patoux and C. Masquelir reported that LiTiPO 5 / Super P carbon (SP carbon; MMM Carbon, Belgium) electrodes worked as active materials using cyclic voltammetry (CV) measurements and galvanostatic intermittent titration techniques (GITT).…”
Section: Introductionmentioning
confidence: 99%
“…17 In contrast to electron based techniques hard x-ray scattering techniques such as x-ray diffraction (XRD) and x-ray reflectivity (XRR) are only slightly affected by gases or liquid. A number of studies applying x-ray scattering techniques to study catalytic 18,19 or electrochemical 20,21 systems under realistic or semi-realistic conditions can be found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The additional 230 mA h g −1 capacity is most probably due to the reduction of the electrolyte over the positive electrode. [25][26][27][28] The first discharge can be segregated to three voltage regions (Fig. 3).…”
Section: Electrochemical Propertiesmentioning
confidence: 99%
“…The same behavior has been observed in various oxyphosphates such as M 0.5 TiOPO 4 (M = Ni, Co and Fe). [25][26][27][28] Fig . 4 shows the differential galvanostatic profile (dQ/dV) of the Na 2 Co 2 Fe(PO 4 ) 3 material.…”
Section: Electrochemical Propertiesmentioning
confidence: 99%